Citizenship education and heritage: a proposal for promoting culture and sustainable development in Viñales valley - Torres Cruz, Eusebio; Acosta González, Geobel; Sierra Socorro, Julio Jesús (Transformación, 2024)
Objective: The study aims at describing a set of activities to promote citizenship education for education and heritage culture enrichment, in order to stimulate individuals’ sustainable participation in preserving and protecting Viñales valley diversity.Methods: The authors rely on theoretical methods such as the critical analysis of documents related to heritage education and legal norm ruling the interrelation of the local society to the environment. The systemic approach, the analysis-synthesis and inductive deductive methods, and comparative studies, as well as observation and interviews make possible to characterize the geographical environment and to configure a framework viewing citizenship education as a process and educations as its object and immediate result.  Results: The main finding is a theoretical framework of a set of activities promoting citizenship education favoring education and cultural heritage enrichment. This framework includes the general principles and the description of its structural components.Conclusions: The set of activities devised favor citizenship and heritage education of Viñales inhabitants. According to the assessment just completed resulting in a high level of knowledge and participants’ satisfaction, and a medium level of transformation of participants’ performance, that, naturally, demands further attention and maturation.
Keywords: Citizenship education; cultural heritage; heritage culture; sustainable development